Correction: Crystalline boron monosulfide nanosheets with tunable bandgaps. Issue 9 (18th February 2022) - Kusaka, Haruki; Ishibiki, Ryota; Toyoda, Masayuki; Fujita, Takeshi; Tokunaga, Tomoharu; Yamamoto, Akiyasu; Miyakawa, Masashi; Matsushita, Kyosuke; Miyazaki, Keisuke; Li, Linghui; Shinde, Satish Laxman; Lima, Mariana S. L.; et al.
Abstract : Correction for 'Crystalline boron monosulfide nanosheets with tunable bandgaps' by Haruki Kusaka et al., J. Mater. Chem. A, 2021, 9, 24631–24640, DOI: ; 10.1039/D1TA03307G .